Analysis of the body composition of Paralympic athletes: Comparison of two methods - De Aquino Lemos, V.; Da Silva Alves, E.; Schwingel, P. A.; Pereira Rosa, J. P.; Da Silva, A.; Winckler, C.; Vital, R.; Aparecido De Almeida, A.; Tufik, S.; De Mello, M. T. (European Journal of Sport Science, 2016)
Body composition is a physiological variable associated with physical activity and, in some cases, is related to athletic performance. Our objectives were to describe the body composition of participants in three distinct Paralympic sports and to compare the values of body density and estimated body fat obtained from the Paralympic athletes on the National Team by air-displacement plethysmography (ADP) and by the anthropometric method (skinfolds (SFs)). The sample consisted of 70 volunteers of both genders. The body composition of the volunteers was evaluated using the ADP in a Bod Pod® and seven SFs. There were no significant differences between the values obtained by ADP and SF for body fat percentage (p = .58) and body density (p = .49). Analysis by Bland-Altman plots showed mean differences of 0.56 ± 4.94 (-9.12-10.23) and -0.0017 ± 0.0113 (-0.024-0.020) for body fat percentage and body density, respectively. In conclusion, body composition analyses of Paralympic athletes by the ADP and SF methods show similar results, and ADP should be used as the first option when available. When the use of ADP is not possible, estimating body density and fat percentage by SF is a viable alternative for Paralympic athletes when future comparisons will use the same analysis method.